Noteworthy bird records from the southern section of the Mexican Plateau - Mónica E. Riojas-López; Eric Mellink (Huitzil, 2019)
In order to increase knowledge about birds in the Llanos de Ojuelos, a semi-arid and highly anthropized region with significant information gaps on biodiversity, we present records of 12 species, obtained between 2000 and 2019. These include extensions of their distribution areas, altitudinal ranges, habitats. Most of these species can be considered occasional or accidental visitors, but others could be permanent residents in the region. Our Black-capped Vireo record suggests a reconsideration of the proposed migratory route. The observations presented and analyzed here illustrate the paucity of knowledge of avian diversity in the region and on the mobility of species at scales greater than regional. More work would likely result in more accurate distribution maps and migration hypotheses, especially under the scenario of global climate change.